2019
DOI: 10.1038/s41598-019-50362-2
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of local ancestry and evidence of adaptation in admixed populations

Abstract: Admixed American populations have different global proportions of European, Sub-Saharan African, and Native-American ancestry. However, individuals who display the same global ancestry could exhibit remarkable differences in the distribution of local ancestry blocks. We studied for the first time the distribution of local ancestry across the genome of 264 Brazilian admixed individuals, ascertained within the scope of the Brazilian Initiative on Precision Medicine. We found a decreased proportion of European an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 75 publications
(138 reference statements)
4
46
3
1
Order By: Relevance
“…In summary, the maximum proportion of individuals with deleterious alleles in the population from southeastern Brazil is much lower than the one we recorded in the admixed population from northern Brazil. One possible reason for this discrepancy is the greater contribution of Amerindian ancestry to the northern (Amazonian) population in comparison with that from southeastern Brazil, since the first has an average of 30% and the second has a medium of 8.8% of Amerindian genetic background [17,18,30].…”
Section: Plos Onementioning
confidence: 99%
“…In summary, the maximum proportion of individuals with deleterious alleles in the population from southeastern Brazil is much lower than the one we recorded in the admixed population from northern Brazil. One possible reason for this discrepancy is the greater contribution of Amerindian ancestry to the northern (Amazonian) population in comparison with that from southeastern Brazil, since the first has an average of 30% and the second has a medium of 8.8% of Amerindian genetic background [17,18,30].…”
Section: Plos Onementioning
confidence: 99%
“…Similar to other admixed American populations, the Brazilian population is derived from sub-Saharan African, European, and Native American populations 25 28 . However, we cannot use other admixed American populations as a reference for Brazilians due to differences in the proportions of ancestral populations from which the current Brazilian and other admixed Americans are derived 9 11 , 28 , 29 . In this specific case, genomic markers detected in other admixed American populations have the potential to mischaracterise the genomic landscape of interest because the allele frequencies of some genetic markers are population-specific.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a study on admixed Brazilians found PAS acting on a Native American haplotype encompassing the PPP1R3B gene, which is involved in glycogene synthesis. Such variants in Mexicans and Brazileans may have been advantageous due to increased fat and glucose storage under a restrictive diet environment ( Secolin et al. 2019 ; Ko et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%